(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: Pneumonia remains a leading cause of childhood morbidity and mortality despite the presence of effective preventive and curative management. The factors at presentation that determine prognosis particularly mortality among children with pneumonia have not been fully characterised in resource-poor centres. Objectives: This study set out to determine the hospital prevalence, pattern of presentation, associated risk factors, and determinants of deaths among children admitted with community-acquired pneumonia in Ilesa. Methods: We carried out a retrospective review of 352 children managed for pneumonia at the Wesley Guild Hospital, Ilesa, Nigeria over a three year period (2011 to 2013) by analysing hospital records. History, clinical features and laboratory findings at presentation were compared in children who survived and those who died. Binary logistic regression analysis was used to determine the independent predictors of mortality. Results: Pneumonia accounted for 23.5% of the 1470 total admission among children one month - 15 years during the period with a male preponderance of 1.4:1 and 84.9% of the children being less than two years. Sixty (17.0%) of the children were undernourished with 12 (3.4%) being severely wasted. Radiological pneumonia was observed in 44.0% of the children, 116 (33.3%) presented with heart failure while 18 (5.1%) had underlying cardiac lesions. Thirty-five (9.9%) of the children died. Children with pneumonia who in addition had concurrent measles infection, heart failure, cyanosis, head nodding and severe undernutrition were at increased risk of death. (p < 0.05) Severe wasting independently predicts mortality among the children. (RR = 5.86; 95% CI = 1.34 – 12.11; p = 0.01). Conclusion: Children with pneumonia who in addition had measles, heart failure, cyanosis and severe protein energy malnutrition should be aggressively managed because they are at increased of dying